THE EFFECT OF SELF-EDITING ACTIVITY TOWARDS STUDENTS’ WRITING SKILL IN RECOUNT TEXT FOR TENTH GRADE STUDENTS OF SMA NEGERI 2 AMLAPURA - Putra, I Komang Janu Prianda; Dewi, Ni Nyoman Padma; Dewi, Ni Kadek Sintya (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Nowadays, students are required to be independent learners, and it becomes more challenging in this pandemic. This research investigated whether or not there is a significant effect of self-editing activity on students’ writing skill for tenth-grade students. This study focused on how self-editing activity for tenth-grade students affects students’ writing quality and limited writing recount text. Experimental quantitative method was used in this study, especially in Post Test Only Control Group Design. Two tenth-grade students in SMA N 2 Amlapura were selected and given different treatments. The experimental group was assigned self-editing activity in their learning process, while the control group was taught using the conventional teaching method. The data were obtained from students’ post-test scores. The quantitative analysis demonstrated a significant effect of self-editing activity on students’ writing recount text. The findings showed that students treated using self-editing activity got better mean scores than the students in the control group. Students were assisted in self-editing activities in their writing class by using correction symbols as their guidance. Also, the effect size calculation verified that the size was medium in online teaching and learning.